Comunidade política e bem comum na Chronica civitatis Ianuensis de Iacopo de Varazze - Alessio Alonso Alves (2014)
The aim of this study is to establish an analysis of the concepts of Political Community and Common Good developed by friar Preacher and archbishop of Genoa Iacopo Varazze in his Chronica civitatis Ianuensis ab origine ad annum usque MCCXCVII (Chronicle of the city of Genoa, from its foundation to the year 1297), a text composed in the last decade of the thirteenth century. To do so, first we will clarify the importance that these issues had at the time, showing how they were discussed and deployed in political action. Subsequently, we will focus on the moment and the producing process of the chronic, debating its structural and compositional characteristics and the goals that led the author to compose it. Finally, we will develop a careful examination of the uses made of the term communitas and of expressions that bears the the sense of common good (like bonum commune, utilitas commune and respublica) in the Chronica.